(untitled) (Revista Internacional de Folkcomunicação, 2019)
This paper analyses the folk-communication performances of project Teatro na Usina (Theater in the Plant), in the district of Bebelândia, Santa Rita city-PB, Brazil’s northeast. The aim is to check how the cultural initiative cooperates with the protagonism, empowerment and citizenship. The applicated method was a study case, during November/2016, including semi-structured interviews, with the intention of reveling the communities’ voices about the proposal and improvements caused by project. The cultural performances, after the conclusions, contribute to the local development, within social and educational aspects. Local development; Performances; Folk-communication; Education.